Respuesta :

Answer:

The solution to the equation is;

[tex]\begin{gathered} x=-3+i \\ or \\ x=-3-i \end{gathered}[/tex]

Explanation:

Given the equation below;

[tex]4x(x+6)=-40[/tex]

Expanding the bracket we have;

[tex]4x^2+24x=-40[/tex]

dividing through by 4;

[tex]\begin{gathered} \frac{4x^2}{4}+\frac{24}{4}x=-\frac{40}{4} \\ x^2+6x=-10 \end{gathered}[/tex]

To solve by completing the square, let us add the square of half of 6 to both sides;

[tex]\begin{gathered} x^2+6x+(\frac{6}{2})^2=-10+(\frac{6}{2})^2 \\ x^2+6x+9=-10+9 \\ x^2+6x+9=-1 \\ (x+3)^2=-1 \end{gathered}[/tex]

taking square roots of both sides;

[tex]\begin{gathered} x+3=\sqrt[]{-1} \\ x+3=\pm i \end{gathered}[/tex]

So;

[tex]\begin{gathered} x=-3+i \\ or \\ x=-3-i \end{gathered}[/tex]

Therefore, the solution to the equation is;

[tex]\begin{gathered} x=-3+i \\ or \\ x=-3-i \end{gathered}[/tex]